Experimental investigation of hybrid fibre reinforced polymer composite material and its microstructure properties. (2021) - Dhinakaran, V.; Vijayakumar, M.D.; Muthu, G.; Sathish, T.; Bupathi ram, P.M.
Abstract: The use of composite materials is an increasing area of interest. In today's world most of the things are made by composites, due to their ability to produce higher mechanical properties that are very much needed by today's economy. The composite material produces the combined properties of two or more materials such as metals, polymers, ceramics, etc. The composites provide high strength, durability, low weight and density, and several other mechanical properties. This paper investigates the mechanical properties of the hybrid fiber reinforced polymer composite material. The tensile test, flexural test and hardness test were carried out and the results were analyzed. The composite material showed better characteristics than the other materials.